The impact of the dose and timing of epicutaneous allergen exposure on the manifestation of allergic responses in vivo - Singh, Tarandeep (My University, 2016)
Exposure to sufficiently high allergen levels of some allergens appears to protect against the development of allergic diseases, and has also been used to treat established allergic diseases. A reduced prevalence of sensitization and, in some cases, asthma was reported among individuals living in homes with high allergen levels. Furthermore, allergic patients treated with high allergen doses during immunotherapy experienced improved allergic symptoms. The mechanisms for how high allergen exposure may prevent disease are not known and thus, a model in which these mechanisms could be studied in detail is warranted. The objective of this thesis was to model and further characterize the phenomenon of high allergen dose-dependent protection against the development of allergic responses, using a mouse model of epicutaneous sensitization. The impact of exposure to a high dose of cat dander in established allergic disease was also evaluated. Epicutaneous exposure to a high dose of cat dander (150 μg) prevented airway inflammation and airway hyperresponsiveness in genetically different strains of mice, including Th2 prone BALB/c mice. The protective effects against airway inflammation appeared to wane between 10 and 120 days after exposure. When the high dose of cat dander was applied with a sensitizing dose of peanut, peanut induced anaphylaxis was prevented. Exposure to a high dose of another allergen, ovalbumin, was also able to prevent the development of allergic airway disease. In contrast, the high dose of cat dander did not improve established states of allergic disease. Thus, in our mouse model, a high dose of cat dander prevented the development of allergic responses and reflected characteristics of the phenomenon reported in humans. As such, this model may be useful for investigating mechanisms and potential prophylactic options for allergic diseases. As the high dose of cat dander either had no effect or worsened established allergic responses in our model, it is possible that the dose was not high enough to improve disease in sensitized mice. It is also possible that established disease cannot be modified by epicutaneous exposure.
The effect of allergen dose on allergic responses
Keywords: Allergy; immunology; eosinophils